(3HGH GdNdds - (3CMeO Hf GdMSjfs ((3GdeTgO GdZQhjs)
(3ChdgG (B:s
(3aj HjGf CMcGe GdNdd hgh(B...(3GdaQLI Hjf GdTjFjf(B...s
(3BNQgG (B:s
(3HfGA Ydi GNJQfGg aj GYJHGQ GdTQhW GdeYJHQI aj SLOJj GdUdGI ajgG hEdG adG, gPG BNQ eG bUOfG EjQGOg aj HGH GdNdd(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis